The Legends of Khasak - O V Vijayan (Penguin Books, 1994)
A restlessness born of guilt and despair leads Ravi to embark on a journey that ends in the remote village of Khasak in the picturesque Palghat countryside in Kerala. A land from the past, potent with dreams and legends, enfolds the traveller in a powerful and unsettling embrace. Ravi is bewitched and entranced as everything around him- the villagers, their children whom he teaches in a makeshift school, the elders who see him as a threat; the toddy-tappers, the shamans- takes on the quality of myth. And then reality, painful and threatening, begins to intrude on the sojourner\'s resting place and Ravi begins to understand that there is no escape from the relentless dictates of karma Often poetic and dark, always complex and rich, The Legends of Khasak, O.V.Vijayan\'s much-acclaimed first novel, translated into English by the author, is an extraordinary achievement.